Relação com o outro e cuidado de si: um estudo sobre a noção de mestria no curso L herméneutique du sujet, de Michel Foucault - Francisco, Alessandro de Lima (2011)
This study aims at rebuilding Michel Foucault s elaboration during his course presented in 1982, and called L herméneutique du sujet, on the following theme: mastering, that is, the relationship between master and disciple, through a systematic reading of his classes, and a final proposal to ponder on Philosophy and Education, as well as on the understanding of Michel Foucault s thought. This study allows a new reading perspective of this thinker s writings based on the nation of mastering, re-emphasizing the theme of the relationship with the other on the general perspective of taking care of oneself